Cost and utility in immunocompromised subjects who developed herpes zoster during the randomized V212 inactivated varicella-zoster vaccine (ZVIN) trial. (1st November 2020) - Eriksson, Jennifer; Hunger, Matthias; Bourhis, François; Thorén, Robyn; Popmihajlov, Zoran; Finelli, Lynn; Jiang, Yiling
ABSTRACT: Objectives : Immunocompromised subjects are at increased risk for herpes zoster (HZ) and HZ-related complications, such as post-herpetic neuralgia (PHN). We describe health utilities, health care resource utilization (HCRU), productivity loss and health care costs in recipients of autologous hematopoietic stem-cell transplantation (Auto-HSCT) who developed confirmed HZ in the phase 3 clinical trial. Methods : HCRU, costs, and EQ-5D-3L utility were assessed for 155 confirmed HZ cases observed after receiving inactivated varicella-zoster virus (VZV) vaccine (ZVIN ) or placebo. In a prospective, longitudinal 6-month follow up, costs and utilities were analyzed for two health states, HZ without PHN and HZ with PHN. Results : There was a clinically relevant difference in utility between HZ without PHN (mean 0.814) and HZ with PHN (0.729). The disutility for HZ without PHN was estimated to −0.117 and to −0.186 for HZ with PHN. Direct costs (2017 USD) associated with a HZ without PHN episode and HZ with PHN episode was estimated at $3, 412 and $3, 711, respectively, of which hospitalizations accounted for 90% of the costs. Expert opinion: Both HZ and PHN are associated with considerable disutility in recipients of Auto-HSCT. Costs were comparable to published estimates in other immunocompromised subjects. The trial is registered at ClinicalTrials.gov (CT.gov identifier: NCT01229267).